PRE-COMPETITION PREPARATION OF 10-12 YEAR OLD AMATEUR JUDOKAS BASED ON THE APPLICATION OF MESOCYCLES AIMED AT LOAD SELECTION. - Sherjonov Baxtiyar Jalg‘asbay ulı (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The relevance of the problem under study is determined by the extremely important significance of the rational design and implementation of the pre-competition training stage, which determines the level of sports achievements of amateur athletes in the main competitions of the season. A model of a two-month pre-competition training program for young judokas aged 10-12 was developed and tested. This model is based on the use of targeted mesocycles of total loads. The introduction of the experimental program into the training process ensured a significant increase in the level of general and special physical preparedness of athletes.